Changing the Conversation: From Suffering with Dementia Through Dementia as a Disability Rights Issue, to a Deeper Theological Perspective. (3rd April 2019) - Matthews, Pia
Abstract: The author explores how the conversation has changed from "suffering from" to "living well with" dementia. Under the influence of disability studies, notably the social model of disability, attempts have been made to expunge the language of suffering from the dementia experience and focus instead on human rights and enabling choice. These attempts have been subject to some criticism. The author argues that a theological perspective, primarily seen through the writing of Pope John Paul II, can help to do justice to both living well and the realities of suffering in dementia.